2016
DOI: 10.1186/s13049-016-0242-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-time tablet-based resuscitation documentation by the team leader: evaluating documentation quality and clinical performance

Abstract: BackgroundPrecise and complete documentation of in-hospital cardiopulmonary resuscitations is important but data quality can be poor. In the present study, we investigated the effect of a tablet-based application for real-time resuscitation documentation used by the emergency team leader on documentation quality and clinical performance of the emergency team.MethodsSenior anaesthesiologists either used the tablet-based application during the simulated resuscitation for documentation and also used the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…To correctly fill out reports and subsequently analyze adherence to CPR guidelines, real-time documentation by an attending professional using a tablet may improve data quality and accuracy without compromising team performance. (32) …”
Section: Discussionmentioning
confidence: 99%
“…To correctly fill out reports and subsequently analyze adherence to CPR guidelines, real-time documentation by an attending professional using a tablet may improve data quality and accuracy without compromising team performance. (32) …”
Section: Discussionmentioning
confidence: 99%
“…Fung and colleagues suggested that the lack of an objective measurement of team performance is one reason for this paucity of data [15]. While, for example, chest compression rate and depth can nowadays be tracked [16] and technical solutions help to document resuscitations more precisely [17], teamwork behaviour is not easy to measure, especially in real-life situations. Such information is not only relevant for research but also a necessity to inform debriefings after resuscitation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although accurate recording of delivery room resuscitation is important for complete medical documentation, research and quality assurance initiatives, resuscitation documentation is often incomplete and/or inaccurate 2–4. Schilleman et al reported that retrospective documentation accurately reflected the mode of respiratory support in 83%, FiO 2 use in 57% and initial HR assessment in 37% delivery room resuscitations 2.…”
Section: Discussionmentioning
confidence: 99%
“…Video recording captures more objective and consistent information than both retrospective and in-person documentation 2–4. However, technical and implementation barriers limit the reliability of video recording,5 as evident by the seven resuscitations excluded from our study due to incomplete recordings.…”
Section: Discussionmentioning
confidence: 99%